2020
DOI: 10.1136/jitc-2020-000816
|View full text |Cite
|
Sign up to set email alerts
|

FcγRIIB engagement drives agonistic activity of Fc-engineered αOX40 antibody to stimulate human tumor-infiltrating T cells

Abstract: BackgroundOX40 (CD134) is a costimulatory molecule of the tumor necrosis factor receptor superfamily that is currently being investigated as a target for cancer immunotherapy. However, despite promising results in murine tumor models, the clinical efficacy of agonistic αOX40 antibodies in the treatment of patients with cancer has fallen short of the high expectation in earlier-stage trials.MethodsUsing lymphocytes from resected tumor, tumor-free (TF) tissue and peripheral blood mononuclear cells (PBMC) of 96 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…Targeting the membrane proximal domains appears optimal for both deletion and agonism; with the latter strongly driven by isotypes with low A:I ratios such as mIgG1. Lowering the A:I ratio can be attained in many different ways, for example, by increasing the affinity for FcγRIIB, which has been shown to mediate more effective agonism for anti-CD40 mAb 52 and a recent paper showed that this may also be true for OX40 using a clinically relevant antibody 53 in vitro but as yet it is unclear whether this will be true in vivo for anti-hOX40 mAb. These findings have implications for the design of the next generation of anti-hOX40 mAb for the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting the membrane proximal domains appears optimal for both deletion and agonism; with the latter strongly driven by isotypes with low A:I ratios such as mIgG1. Lowering the A:I ratio can be attained in many different ways, for example, by increasing the affinity for FcγRIIB, which has been shown to mediate more effective agonism for anti-CD40 mAb 52 and a recent paper showed that this may also be true for OX40 using a clinically relevant antibody 53 in vitro but as yet it is unclear whether this will be true in vivo for anti-hOX40 mAb. These findings have implications for the design of the next generation of anti-hOX40 mAb for the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Publically available RNA-sequencing data (GSE152904; GSM4629190, GSM4629187, GSM4629184, and GSM4629181) were used for analysis of comprehensive cytokine expression profiles in human CD4+ T cells induced by OX40 signaling (GEO accession). CD4+ T cells were stimulated in vitro in the presence of anti-CD3/CD28 activation beads, with or without agonistic OX40 antibody for 3 to 5 days, after which RNAsequencing was performed to evaluate OX40-mediated transcriptional changes (34). Gene expression was quantified by RSEM (v1.2.14).…”
Section: Rna-sequencing Analysismentioning
confidence: 99%
“…Platelet secretion of vascular endothelial growth factors, migration, and proliferation of endothelial cells have an induction effect, increased vascular permeability, tumor cell penetrating machine vascular metastasis, and invasive chances [ 12 , 13 ]. RDW reflects the heterogeneous parameters of red blood cell size and peripheral blood [ 14 , 15 ]. In addition, research shows that various factors will affect PLR and NLR individual test results and reduce sensitivity and specificity [ 16 ].…”
Section: Discussionmentioning
confidence: 99%